Actin reorganization in hippocampal neurons may play a role in early learning and memory impairment after propofol anesthesia in rats - Xuena Zhang; Jie Li (Journal of International Medical Research, 2023)
Objectives To observe changes in actin and dendritic spines in the hippocampus after propofol anesthesia, and to evaluate the role of these changes in subsequent learning impairment in both young (3-month-old) and aged (20-month-old) male rats. Methods The shuttle box test was used to evaluate learning from 1, 3, 7, or 14 days after anesthesia. Both F-actin content and dendritic spines in the hippocampal CA1 region were observed using immunofluorescent staining and western blot assays. Results The latency of the escape response was significantly prolonged until 7 days after anesthesia in the aged rats, and their learning curves were shifted. Dendritic spines were also decreased in the aged rats within 7 days after anesthesia, and F-actin content was significantly increased until 14 days after anesthesia. Conclusions Learning was inhibited after propofol anesthesia, especially in aged rats. The over-polymerization of actin and subsequent reorganization of dendritic spines in the hippocampus may be responsible for this learning impairment. Our findings suggest that synaptic plasticity may be an underlying mechanism of perioperative neurocognitive disorders.